Adrenal hemorrhage in the neonatal intensive care unit: a four-year experience - Fedakar, Atiye (The European Research Journal, 2019)
Objectives: Adrenal hemorrhage is relatively uncommon and usually underestimated. This study aimed to review the clinical, predisposing factors and ultrasonographic findings of adrenal hemorrhage newborns treated in hospital neonatal intensive care unit. Methods: The medical records of 14 newborns with adrenal hemorrhage who had been admitted to our neonatal intensive care unit were retrospectively reviewed. Results: During the study period, 1979 patients were admitted to our neonatal intensive care unit. Throughout the four-year follow-up of patients in the neonatal intensive care unit, adrenal hemorrhage was diagnosed with ultrasonography in 14 (0.70%) infants; thirteen of them were term babies, one of them was a premature baby. Among these 14 patients, 10 (71.4%) were males, 4 (28.6%) were females. The average birth weight was 3809.1 ± 358.5 g. Neonates had risk factors such as: birth trauma in 5 (35.7%) newborns, perinatal asphyxia in 4 (28.6%) newborns, sepsis in 2 (14.3%) newborns, large gestation age in 3 (21.4%) newborns. Resuscitation was performed in 7 (50%) infants in the delivery room. The most common clinical presentations of the newborn with adrenal hemorrhage was hypotonia and lethargy (n = 5; 35.7%). Nine (64.3%) newborns had adrenal hemorrhage on the right side, three (21.4%) of them had bilateral adrenal hemorrhage, and the last two (14.3%) had adrenal hemorrhage on left side. Resolution time of adrenal hemorrhage was a minimum of one month and maximum of three months in ultrasonographic follow-up. Conclusions: If there are anamneses of strenuous and traumatic deliveries, and any clinical suspicion, ultrasonography should be performed to exclude adrenal hemorrhage, since it is non-invasive, and also straightforward to apply. In babies with hematomas that are increasing in size, adrenocorticotropic hormone and cortisol levels should be analyzed to prevent any possible adrenal insufficiency, even if there is no clinical sign.